Competing in the Era of Industrial Revolution 4.0 and Society 5.0 - Lena Ellitan (Jurnal Maksipreneur, 2020)
The industrial revolution 4.0 presents challenges that must be faced by the business world, namely the lack of adequate HR (Human Resource) skills, the problem of security of communication technology, the reliability of the stability of production machines, the inability to change by stakeholders, and the number of job losses due to automation. Society 5.0 offers a human-centered society that makes a balance between economic progress and the resolution of social problems through a system that is highly connected through cyberspace and the real world. If society 4.0 allows anyone to access also share information on the internet. Society 5.0 is an era where all technology is part of humanity itself. To take advantage of opportunities and answer the challenges of the industrial revolution 4.0, Indonesian people in particular are required to have data, technology and human literacy capabilities. Data literacy is needed by HR to improve skills in processing and analyzing big data for the benefit of improving public and business services. Technology literacy shows the ability to utilize digital technology to process data and information, while human literacy must be mastered because it shows the element of soft skills or the development of individual character to be able to collaborate, be adaptive, and innovative. Indonesia is demanded to be able to follow industry 4.0 workflows juxtaposed with society 5.0. The need for human resources in several business fields is still very massive if all of them are carried out by robotics. Indonesia is a developing country with a fairly dense population that is certainly able to align between the needs of industry 4.0 and society 5.0. Leadership in organizations must stay alive so that every innovative competitive strategy is able to run with the existing vision. To go to the era of society 5.0 the government is obliged to continuously control it.